(untitled) - Payne, V. Gregory (Boston, 2012)
This topically organized text provides a comprehensive introduction to lifespan motor development and includes the most current research findings available in the field. The text takes a lifespan approach to development, with thorough coverage of prenatal, childhood, adolescent, and adult development. Theoretical concepts are conveyed through language appropriate for undergraduate students. This is the only lifespan motor development text that presents both the component approach and the total body approach for analyzing the basic fundamental and object control skills of childhood.
Keywords: Human mechanics,Cơ học người